2018
DOI: 10.5815/ijisa.2018.03.06
|View full text |Cite
|
Sign up to set email alerts
|

Solving School Bus Routing Problem using Genetic Algorithm-based Model

Abstract: School Bus Routing Problem is an optimization problem which falls under the class of the Vehicle Routing Problem. It involves the use of a fleet of vehicles to efficiently and optimally transport students to and from their schools. To solve this problem, optimal school bus routes are found by minimizing the number of buses, the number of routes and the total distance traversed along all routes. Manual routing of school buses have led to creation of many routes, increased number of buses and several buses navig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(29 reference statements)
0
6
0
3
Order By: Relevance
“…In the literature, SBRP has been categorized under different sub-groups depending on the considered problem: bus stop selection, bus route generation, and bus route scheduling, etc. Among these problems, bus stop selection problem [5,6,7] identifies a bus stop location for each student, bus route generation problem [8,9,10,11,12] determines the visiting sequences of predetermined bus stops, and bus route scheduling problem [13,14] includes a time dimension to determine exact loading time of the students. The main focus of this work will be on the route generation part since the company has already fixed the possible pickup locations (bus stops), and the time of loading at each stop is not their primary focus, which is post adjustable.…”
Section: Employee Shuttle Bus Routing Problemmentioning
confidence: 99%
“…In the literature, SBRP has been categorized under different sub-groups depending on the considered problem: bus stop selection, bus route generation, and bus route scheduling, etc. Among these problems, bus stop selection problem [5,6,7] identifies a bus stop location for each student, bus route generation problem [8,9,10,11,12] determines the visiting sequences of predetermined bus stops, and bus route scheduling problem [13,14] includes a time dimension to determine exact loading time of the students. The main focus of this work will be on the route generation part since the company has already fixed the possible pickup locations (bus stops), and the time of loading at each stop is not their primary focus, which is post adjustable.…”
Section: Employee Shuttle Bus Routing Problemmentioning
confidence: 99%
“…Understanding Human Mobility Pattern has significant impacts and enables various applications such as urban planning [35], region function analysis [31,32], hotspots detection [36], driving route recommendation [11,33], and bus route planning [4,5,21,24]. Bastnai et al [4] grouped taxi trips into clusters and identified a route connecting multiple clusters to maximize the sum of each connected trip cluster without considering other constraints such as time.…”
Section: Related Workmentioning
confidence: 99%
“…El SBRP se encuentra clasificado en la literatura como un problema de optimización combinatoria [5], el cual busca diseñar rutas para una flota de buses escolares con el objetivo de minimizar el tiempo y los costos [6] al prestar el servicio de transporte de estudiantes hacia sus respectivas escuelas o colegios en áreas rurales o urbanas.…”
Section: Revisión De La Literaturaunclassified
“…Por el lado de las meta heurísticas se encuentran investigaciones en ruteo de buses escolares que emplean búsqueda tabú [14], algoritmos genéticos [5], optimización por enjambre de partículas [18], colonia de hormigas [19], la meta heurística GRASP [20] entre otras. Sim embargo, no se encuentran investigaciones que empleen la búsqueda tabú granular en el problema del rute de buses escolares, a pesar de que ha gozado de gran aceptación en problema de ruteo de vehículos de carga [21].…”
Section: Revisión De La Literaturaunclassified
See 1 more Smart Citation